When to Preach About Poverty: How Location, Race, and Ideology Shape White Evangelical Sermons - Guhin, Jeffrey (Journal for the scientific study of religion, 2023)
Social scientists have long been interested in how intergroup contact or elite messaging can reduce or eliminate racial biases. To better understand the role of religious elites in these political questions, we show how a church location's income and racial characteristics interact with racial and economic ideologies to shape the political content of sermons. Testing our theories through both quantitative and qualitative analysis of an original data set of more than 102,000 sermons from more than 5200 pastors, we show that contact is only effective as a means of decreasing prejudice to the extent that actors—in our case, pastors—are ideologically capable of reconciling their potential role in economic inequality. White Evangelical pastors rarely preach about issues of poverty or racial justice overall, but the context of the preaching matters. We find that the greater the share of Black population there is in a church community, the less likely White Evangelical pastors are to mention issues of poverty or racial justice, and when they do mention it, they hold to ideological commitments that avoid blaming systems for racialized economic inequality.